Analisis Pengetahuan Pajak, Kesadaran Wajib Pajak, Sanksi Pajak dan Pengaruhnya Terhadap Kepatuhan Wajib Pajak Orang Pribadi pada KPP Pratama Tangerang Barat - Samino Hendrianto; Nursimah Dara; Masturo; Gita Ririn Fitriani (Jurnal Multidisiplin Madani, 2022)
The purpose of this study was to examine Tax Knowledge, Taxpayer Awareness, Tax Sanctions, and Its Effect on Individual Taxpayer Compliance (WPOP) at KPP Pratama, West Tangerang. The population of this study includes all taxpayers registered at the West Tangerang KPP Pratama for the 2018-2020 period. The sampling technique used incidental sampling technique. Based on the predetermined criteria obtained 100 respondents. The type of data used is primary data obtained from the questionnaire results. The analytical method used is multiple linear regression analysis. The results of the study show that Tax Knowledge has no effect on Taxpayer Compliance. Meanwhile, Taxpayer Awareness and Tax Sanctions have a positive effect on Individual Taxpayer Compliance.